Peningkatan Kapasitas Masyarakat Desa Tegalwangi melalui Pelatihan Digital Marketing - Dowan Rahma Seta; Marita Yayang Santosa; Sofi Cordova Andalusia; Alfian Takbirryansyah; Caesar Daffa Parahitha; Annisa Syifa Sanjaya; Nur Akhillah Roikhatul Jannah; Ahmad Fada Prasetya; Okke Silvi Febriyanti; Christopher Alvandio; Inas Thohirah Farianto; Dinda Natalia Sasabila; Yevia Clara Tarigan; Brilliant Tri Valentino; Zalfa Alayya Eka Putri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The GAS TANCAP (Chili Planting Elementary School Children's Movement) and Eco Print activities are activities that aim to develop the character of creativity and caring for the surrounding environment in elementary school children. Apart from that, this activity also aims to enable elementary school children to fill their free time with activities that are beneficial for them. This social project activity was carried out at SDN Badean 03 which is located in Bondowoso District, Bondowoso Regency, with a total number of students from grade 1 to grade 6 of 50 students. The method used in this social project is the integrated learning method. This method includes providing material or direction to students, then students practice the material that has been given outside of class. The results obtained from this social project are that students can find out how to cultivate chilies properly and correctly, and students gain insight into how to make batik using the Eco Print technique which comes from natural materials. The hope is that students at SDN Badean 03 can apply the knowledge they have gained in their daily lives, and become the successors of a nation that cares more about and loves the environment around them.